Hubungan Pola Asuh Orang Tua terhadap Kejadian Sibling Rivalry pada Anak di RW 002 Kelurahan Bukit Tempayan Kecamatan Batu Aji Kota Batam: The Relationship of Parenting Pattern with the Rivalry Sibling at RW 002 Kelurahan Bukit Tempayan Batu Aji Kota Batam - Panggabean, Septi Maisyaroh Ulina (Jurnal Surya Medika (JSM), 2021)
The way parents educate and raise children is influenced by many factors such as culture, religion, customs, beliefs, and personality of the parents. This study aimed to determine the relationship between parenting parents with the incidence of sibling rivalry in children. This study is an analytical cross-sectional correlation, the total population of samples taken with accidental sampling technique, the sample size of 20 respondents. The results showed the majority of children experience sibling rivalry events, from the results of the Chi-Square test of goodness of fit p-value of 0.001 with a significance level of 0.05, meaning that there is a significant relationship between parenting parents with the incidence of sibling rivalry. From this study, it can be seen that most of the respondents who apply pemanja authoritarian parenting and sibling rivalry occurs in children. Parents need to know and understand in applying parenting according to the stage of the child's behavior. Necessary counseling and guidance on parenting books that fit the child's development phase.